The Influence of Chinese Machiavellianism and Moral Identity on the Level of Anxiety in Moral Dilemma Situations in Chinese Students - Tang, Shujun; Li, Kai (Frontiers in Psychology, 2021)
Based on the values conflict theory, this study examines the influences of Machiavellianism and ethical values on anxiety in college students when they face moral dilemmas. Questionnaires on the Chinese equivalent of Machiavellianism, moral identity, and anxiety were completed by 115 Chinese college students. The results suggest that Machiavellianism and ethical values influence anxiety, and the interaction between ethical values and Machiavellianism is significant—among individuals with high ethical values, those with high levels of Machiavellianism exhibit markedly higher levels of anxiety than those with low levels of Machiavellianism. However, among individuals with low ethical values, there is no difference in anxiety between those with low or high levels of Machiavellianism. This research, depicting complex relationships among anxiety, Machiavellianism, and ethical values, suggests that leading people to do good deeds not only requires high ethical values, but also necessitates the resistance to negative values such as Machiavellianism.